THE IMPLEMENTATION OF A HEALTH FINANCING SYSTEM THROUGH HEALTH PROMOTION IN INDONESIA - Yana Sylvana; Handar Subhandi Bakhtiar (Yayasan Pendidikan Medika Indonesia, 2022)
Health development is a part of national development. In health development, the goal to be achieved is to increase the optimal level of public health. The principle of public healthcare prioritizes promotive and preventive services. Promotive services are efforts to improve public health for the better. While preventive services are efforts to prevent people from getting a disease. Health insurance applies to every individual (citizen), which should be the obligation of the state to fulfil it without distinguishing one citizen from another. The process of healthcare cannot be separated from health financing. Health costs are the number of funds provided to organize and/or utilize various health efforts needed by individuals, families, groups and communities. Strong, stable and sustainable health financing plays a very important role in the implementation of healthcare in order to achieve various goals of health development in a country. It includes the equal distribution of healthcare and access (equitable access to health care) and quality services (assured quality). This study used a research methodology that reviewed normative juridical carried out by a synthetic study. The deductive conclusions from statements in data sources such as library materials included journals, books, documents, and literature or secondary law such as laws, legal theories, court decisions, expert opinions that are relevant and related to the discussion in this journal. This study was a prescriptive-analytical study in which data synthesis, discussion and conclusions were analyzed qualitatively.